2023
DOI: 10.1656/058.022.0sp1212
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Demography of the Alligator Snapping Turtle (Macrochelys temminckii) in Texas: A 20-Year Perspective

Abstract: Texas contains the southwestern range edge of Macrochelys temminckii (Alligator Snapping Turtle), but there is relatively little published information on this species within the state. To document its range and assess temporal changes in its distribution and demography, we sampled 23 sites from 1999 to 2001. We then resurveyed 22 of these sites and sampled 29 additional sites in 2020-2021. Detection outcomes were consistent between 18 of the 22 resurveyed sites. Sex ratios and body-size distributions were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Although cryptozoic and secretive (Pianka and Vitt 2003), North American scincids are relatively slow (Smith 1997;Watson 2008) and can be easily captured by hand. The freshwater turtle family Chelydridae, represented by only two species in Texas, has received substantial research attention over the past decade due to the imperiled status of Macrochelys temminckii (Gordon et al 2023;Munscher et al 2023;Rosenbaum et al 2023). During this period, a remarkable 19 records have been published for the species, increasing its known range within the state by 54% (Table 2; Dixon 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cryptozoic and secretive (Pianka and Vitt 2003), North American scincids are relatively slow (Smith 1997;Watson 2008) and can be easily captured by hand. The freshwater turtle family Chelydridae, represented by only two species in Texas, has received substantial research attention over the past decade due to the imperiled status of Macrochelys temminckii (Gordon et al 2023;Munscher et al 2023;Rosenbaum et al 2023). During this period, a remarkable 19 records have been published for the species, increasing its known range within the state by 54% (Table 2; Dixon 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since Dixon's passing in 2015 (McAllister and, updated distribution maps have only been created for a few reptilian species (e.g., Bassett 2022;Rosenbaum et al 2023). Herein we assimilate all distribution records for Texas reptiles that have been published since Dixon (2013) went into press and summarize those records with updated maps.…”
mentioning
confidence: 99%
“…During fieldwork in multiple states, we often saw passive gear that had been abandoned and/or missing identifying tags required by state law (e.g., Alabama, Louisiana, and Florida). One study mentioned a higher prevalence of fishing hooks ingested by Macrochelys when more limb lines (fixed lines) were present in the environment (Thomas 2013), while another found an inverse correlation between M. temminckii relative abundance and fishing gear abundance (Rosenbaum et al 2023 [this issue]). Specifically with respect to our data and active fishing, we found that rod and reel angling seemed to result in numerous instances of hooks snagged in appendages or the buccopharynx (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…comm.). Navigable waterways are also frequented by sportsmen and fishermen, and Rosenbaum et al (2023 [this issue]) found a negative correlation between number of trotlines present and Macrochelys captured. Likewise, historically these navigable sites likely experienced higher harvest pressures due to their general accessibility (Boundy and Kennedy 2006).…”
Section: Discussionmentioning
confidence: 99%